Cadmium regeneration within the North Atlantic. Issue 12 (16th December 2015) - Roshan, Saeed; Wu, Jingfeng
Abstract: Cadmium (Cd) incorporated into the benthic microfossils has been widely used in reconstructing the past water circulation in the North Atlantic. This requires a major control by conservative mixing over regeneration process on the seawater cadmium distribution in the North Atlantic. Through coupling the recently reported Cd data at depths below 300 m with quantitative water mass analysis along the GA03 transect, we tested two models for cadmium cycling within the North Atlantic: conservative mixing alone and conservative mixing plus regeneration which is termed as regenerative mixing. The results show that the regenerative mixing model reproduces the observations (slope = 0.99 and R 2  = 0.97) much better than the conservative mixing model (slope = 0.99 and R 2  = 0.88). The regenerative mixing model was applied to estimate the amount of dissolved cadmium regenerated "within" the North Atlantic. This regionally regenerated cadmium contributes to ~10% and >50% of the total cadmium in the North Atlantic at depths >1000 m and 300–1000 m, respectively, indicating that the microfossil‐reconstructed seawater Cd can be attributed to the mixing from the South Atlantic to the North Atlantic with high accuracy for depths below 1000 m, while within 300–1000 m cadmium is more controlled by the regeneration process than the mixing process, complicating the attribution of the microfossil‐reconstructed seawater Cd to the changes in water mass geometry within this 300–1000 m depth range. A regionally and vertically constant Cd/PO4 3− regeneration ratio ~262 pM/µmol/kg was derived from the regenerative mixing model which is comparable with ratios estimated in the recent studies for the North Atlantic. Key Points: Dissolved cadmium distribution was successfully modeled through mixing and regeneration processes In the depth range 300–1000 m, up to >50% of Cd can be controlled by in situ regeneration In below 1000 m, Cd is mainly controlled by conservative mixing of the end‐members